PETATAH-PETITIH PERFORMANCE: ORAL TRADITIONS OF WEST JAVA INDONESIA IN THE CONCEPT OF THE LANGUAGE GENRE - Linda Eka Pradita; Wawan Hermawan (Indonesian language and literature education program Majapahit Islamic University, 2025)
Preservation of oral traditions in an effort to maintain cultural values which are the local wisdom of the community is one of the important issues to be discussed. This is very important in an effort to maintain regional identity and support mental development. Petatah-petitih is an oral tradition in the form of expressions that contain advice, prohibitions, and satire. Expressions are conveyed in informal situations. In official situations, petatah-petitih is spoken in scouting activities for visitors to the Cirebon Kasepuhan Palace. The purpose of this study is to describe the performance. The method used is the ethnographic method. This research approach uses anthropolinguistics which is an interdisciplinary relationship between language and speech behavior (practice). The performance findings are in the form of speaking practice which includes the structure of the petatah-petitih text, the stages of performance of the petatah-petitih, the performer components and the speech function of the petatah-petitih text. The results showed that the performance of petatah-petitih is a performance of advice which consists of persuasive expressions. Persuasive expressions include imperative sentences, invitations, advice and satire.Keywords: culture, oral tradition, performance